The Bad Ones - Albert, Melissa ([Place of publication not identified] : Flatiron Books, 2024)
Teenage Nora uncovers dangerous secrets and eerie local lore surrounding disappearances in her small town, where a teacher and three high school students, including her best friend, go missing.
new ya book 2024 winter.
Keywords: Missing persons; Horror; Supernatural; Paranormal fiction; Friendship